Gadamer’s Hermeneutic Approach in the Concept of Education KH. Hasyim Asy’ari: Pendekatan Hermeneutika Gadamer Dalam Konsep Pendidikan KH. Hasyim Asy’ari - Adi Wijaya; Ehwanudin Ehwanudin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
Education is an integral part that cannot be separated from life. Educationcan realize the progress and civilization of a nation. However, the currentstate of our education is very concerning. The morals and manners of ourstudents are very low. Many of the students like to fight with fellowstudents, acts of violence, they don't even have the shame of holding handswith the opposite sex in public places. This is of course based on the lack ofethics and morals of the students themselves. The concept of education KH.Hasyim Asy'ari is one of the bids in overcoming the moral and ethicalcrisis. Therefore, the concept of education KH. Hasyim Asy'ari is veryrelevant in forming students who are intellectually intelligent and havenoble character in today's modern era. Education in today's modern era ismostly more emphasis on cognitive aspects. So, it is important to examinethe concept of KH's education. Hasyim Asy'ari which emphasizes theprimacy of science and scholars, teaching and learning, student ethics,teacher ethics and ethics towards facilities. In revealing KH's educationalconcept. Hasyim Asy'ari, the author uses Gadamer's hermeneutic approachto review and how the educational concept of KH. Hasyim Asy'ari toanswer the challenges in today's modern era.